2009
DOI: 10.1074/mcp.m900176-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cardiac Myosin-binding Protein C as a Candidate Biomarker of Myocardial Infarction by Proteomics Analysis

Abstract: Acute myocardial infarction (AMI) is a common cause of death for which effective treatments are available provided that diagnosis is rapid. The current diagnostic gold standards are circulating cardiac troponins I and T. However, their slow release delays diagnosis, and their persistence limits their utility in the identification of reinfarction. The aim was to identify candidate biomarkers of AMI. Isolated mouse hearts were perfused with oxygenated protein-free buffer, and coronary effluent was collected afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 40 publications
4
57
0
Order By: Relevance
“…Our data are in line with prior studies examining proteins released into the coronary effluent following ischemia-reperfusion in isolated mouse and rabbit hearts (8,14). In addition to classical necrotic markers such as LDH, creatine kinase, and troponins, the rabbit heart study also identified Crsp3, a LIM domain-containing protein, as being released following ischemia-reperfusion injury (8).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our data are in line with prior studies examining proteins released into the coronary effluent following ischemia-reperfusion in isolated mouse and rabbit hearts (8,14). In addition to classical necrotic markers such as LDH, creatine kinase, and troponins, the rabbit heart study also identified Crsp3, a LIM domain-containing protein, as being released following ischemia-reperfusion injury (8).…”
Section: Discussionsupporting
confidence: 88%
“…We also found Crsp3 in our proteomic analyses, and it appeared to increase, albeit modestly, during necrosis but not apoptosis. The mouse study identified 320 proteins as being upregulated in coronary effluent following 5 min of ischemia (14). Analysis of the data indicated a considerable degree of overlap in the proteins identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jacquet et al identified biomarkers of myocardial infarction by DIGE approach. 12 Meng et al applied 2D-DIGE in combination with matrix-assisted laser desorption/ionization (MALDI)-time of flight/time of flight MS to identify alterations in mitochondrial enzymes that contribute to cardiac hypertrophy in spontaneously hypertensive rats. 13 A combined proteomic and metabolomic analysis has been carried out in murine hearts to obtain mechanistic insights of protein kinase C epsilon (PKCϵ)-mediated cardioprotection.…”
Section: Gel-based Quantificationmentioning
confidence: 99%
“…The potential mis-regulation of MyBP-C-linked kinase signalling in heart disease is likely an underestimated factor, as discussed here (Bardswell et al 2012;Knöll 2012;Kuster et al 2012). While N-terminal fragments due to premature stop-codons do not accumulate detectably in the myocardium of HCM patients, ischaemia-reperfusion injury leads to the proteolytic cleavage of cardiac MyBP-C and the liberation of full-length protein and at least two proteolytic fragments (Jacquet et al 2009;Govindan et al 2012a) that show, in agreement with other studies on N-terminal fragments, tight localisation to the A-band (Govindan et al 2012b). This suggests that such proteolytic MyBP-C fragments might exert ectopic effects on myosin regulation that could contribute to contractile failure in the reperfused heart.…”
mentioning
confidence: 97%